Buffer Zone Management System in Protected Areas of Nepal - Bhusal, Narayan Prasad (The Third Pole: Journal of Geography Education, 2014)
Maintenance of eco-system diversity is often carried out by establishing national parks, wildlife reserves and other protected areas. The fourth amendment of the National Park and Wildlife Conservation Act in 1992 made the provision of buffer zone for protected areas considering buffer zone, an area of 2km in the vicinity of the park could benefit from park revenue (30-50 percent) and in return the community is supposed to participate and assist in park management activities. Between 1996 and 2010 Government of Nepal demarcated buffer zones of 12 protected areas covering a total area of 5602.67 square kilometer in 83 VDCs and two Municipalities of 27 districts where benefiting human population is over 0.9 million. In the buffer zone management programme emphasis has been given on the natural resource management where need of eco-friendly land use practices and peoples participation in conservation for long term sustainability are encouraged. This paper is an attempt to outline the various activities that have been executed under buffer zone management programme of Department of National Park and Wildlife Conservation with the internal resources, local communities and support from UNDP, WWF Nepal, CARE Nepal, NTNC and other various partners for the conservation and development of buffer zones in Nepal. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11558 The Third Pole Vol. 11-12, 2012 Page : 34-44